2012
DOI: 10.1364/ol.37.003612
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YVO_4 amplifier for ultrafast low-power lasers

Abstract: An Nd:YVO4 amplifier consisting of two modules end pumped at 808 nm at 30 W total absorbed power has been designed for efficient, diffraction-limited amplification of ultrafast pulses from low-power seeders. We investigated amplification with a 50 mW, 7 ps Nd:YVO4 oscillator, a 2 mW, 15 ps Yb fiber laser, and a 30 mW, 300 fs Nd:glass laser. Output power as high as 9.5 W with 8 ps pulses was achieved with the 250 MHz vanadate seeder, whereas the 20 MHz fiber laser was amplified to 6 W. The femtosecond seeder al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Nd∶YVO 4 amplifiers pumped at 808 nm have already been proven to deliver high gain. Output powers of around 10 W with gains of about 200 have been obtained with a two stage amplifier and a microchip laser or a fiber laser as seed source [16,17]. Using a more complex setup with a grazing incidence configuration with 4 pass and a phase conjugation mirror, a high gain of 41 dB has also been obtained with 26 W output power [18].…”
mentioning
confidence: 99%
“…Nd∶YVO 4 amplifiers pumped at 808 nm have already been proven to deliver high gain. Output powers of around 10 W with gains of about 200 have been obtained with a two stage amplifier and a microchip laser or a fiber laser as seed source [16,17]. Using a more complex setup with a grazing incidence configuration with 4 pass and a phase conjugation mirror, a high gain of 41 dB has also been obtained with 26 W output power [18].…”
mentioning
confidence: 99%
“…It can be obviously seen that the power gain achieved in the double-pass MOPA architecture is generally larger than that obtained from the single-pass MOPA architecture, especially for the low input seed power. Experimental results also manifestly reveal that the power gain decreases by increasing the input seed power for both configurations, this is a typical behavior for the power amplifier [13], [15], [16]. When the input seed power is changed from 0.8 to 50 W, the power gains are experimentally found to decrease from 8 to 2.16 for the double-pass MOPA frame and from 2.95 to 1.76 for the single-pass MOPA frame, respectively.…”
Section: Comparative Investigation Between Double-mentioning
confidence: 63%
“…To date, most of the Nd:YVO 4 amplifiers are based on the single-pass configuration [12]- [14]. However, some recent works have shown that the double-pass architecture seems to be a more efficient design for scaling the output power of the pulsed oscillator [15], [16]. In this work, an efficient high-power MOPA based on the multi-segmented Nd:YVO 4 crystal is successfully realized for emitting output power greater than one hundred watts in the continuous-wave operation.…”
mentioning
confidence: 99%
“…7. This scheme was already investigated in great detail in previous work [20] and proved to be suitable for amplification of seeders providing few milliwatts average power.…”
Section: Bulk Power Amplifiermentioning
confidence: 98%